A rational inference approach to aphasic language comprehension. Issue 11 (1st November 2016) - Gibson, Edward; Sandberg, Chaleece; Fedorenko, Evelina; Bergen, Leon; Kiran, Swathi
ABSTRACT: Background : It has long been observed that, when confronted with an implausible sentence like The ball kicked the girl, individuals with aphasia rely more on plausibility information from world knowledge (such that a girl is likely to kick a ball, but not vice versa) than control non-impaired populations do. We here offer a novel hypothesis to explain this greater reliance on plausibility information for individuals with aphasia. The hypothesis is couched with the rational inference approach to language processing. A key idea in this approach is that to derive an interpretation for an input string, individuals combine their priors (about messages that are likely to be communicated) with their knowledge about how messages can get corrupted by noise (due to production or perception errors). Aims : We hypothesise that language comprehension in aphasia works in the same way, except with a greater amount of noise, which leads to stronger reliance on syntactic and semantic priors. Methods & Procedures : We evaluated this hypothesis in an act-out task in three groups of participants (8 individuals with aphasia, 7 older controls, 11 younger controls) on two sets of materials: (a) implausible double-object (DO)/prepositional-phrase object (PO) materials, where a single added or deleted word could lead to a plausible meaning; and (b) implausible active-passive materials, where at least two added or deleted words are needed to arrive at a plausible meaning. Outcomes & Results : We observed that, similar to controls, individuals with aphasia rely on plausibility to a greater extent in the DO/PO than in the active/passive alternation. Critically, however, as predicted, individuals with aphasia rely less on the literal syntax overall than either of the control groups, and use their world knowledge prior (plausibility) in both the active/passive and DO/PO alternations, whereas controls rely on plausibility only in the DO/PO alternation. In addition, older persons and persons with aphasia made more errors on the DO structures (which are less frequent than PO structures) independent of plausibility, thus providing evidence for reliance on a syntactic prior, the more frequent structure. Conclusions : These results are as predicted by the rational inference approach to language processing in individuals with aphasia.